Students’ abilities recognition and development model (Professional Pedagogics, 2018)
The article is aimed at construction of the model for recognition and developing the students’ giftedness by controlling, monitoring and adjusting educational process. A high level of intelligence becomes the key to new opportunities, achievements and prospects for status in the social environment of the modern world. In addition, many scientists who study pedagogical systems under different development conditions define such a classification of giftedness that actually indicates that each individual is gifted, only it is necessary to determine the category and direction where he\she can demonstrate this. Five conditions for the development of giftedness were defined to achieve the goal of the study. They include the external and internal qualities of students: general abilities; special abilities in a particular area; special non-intellectual abilities; stimulating environment; random factors.An example of the giftedness recognition and the stages of its development are given. The developed two-stage model is based on a step-by-step system for detection, monitoring and correction of the pedagogical system which is aimed at increasing the creative potential, cognitive activity and motivation for self-improvement of students.The first stage model of recognition and development of giftedness reveals the features of the school educational system performance. The traditional determination of the level of intellectual maturity, the primary formation of cognitive processes that ensure school achievements begins with an interview that allows you to identify areas in which the student feels the most comfortable.
Keywords: pedagogical system; student abilities; development; upbringing; educational process